Post-operative nursing bleeding management in mitral valve repair-re-exploration patient during early post-operative period: A case report - Ulfah Nurrahmani; Riani Siti Hafsah; Reza Widianto Sudjud (Jurnal Keperawatan Padjadjaran, 2024)
Background: One of the first targets of post-operative care for cardiac surgery is to control bleeding. Significant bleeding can affect cardiac function as it can lead to hemorrhagic shock, severe anemia, and cardiac tamponade. Valve surgery has a mortality rate of 3.4%. Mitral valve repair surgery has a mortality rate of 1.2% compared to a valve replacement mortality rate of 4.5%. A quick and appropriate decision in the management of bleeding is one of the factors determining the patient's outcome. This study aims to report on nursing bleeding management in mitral valve repair-re-exploration patient during early postoperative period. This research is qualitative research using the case study method. Case: 59-year-old female with a medical diagnosis of mitral valve prolapse with severe mitral regurgitation of non-significant coronary artery diseases performed mitral valve repair surgery. This case has a score of 1 on the Papworth scale, which means low risk of bleeding. During treatment in the ICU, there was an increase in blood production from the chest tube of 1,670 ml within six hours post-surgery. PT APTT value was within normal range. Bleeding management during early post-operative period was carried out, namely conducting supporting laboratory tests, monitoring hypotension, monitoring urine production, performing chest tube maintenance, giving blood transfusions, fluid management and collaboration for re-exploration. Re-exploration surgery was performed at the sixth hour of post-operative care. Conclusion: The application of post-operative nursing bleeding management in mitral valve repair-re-exploration patient during the early post-operative period provides good clinical outcomes. Effective collaboration (multi-disciplinary teams) between cardiac surgeon, perfusionist, anesthetist, clinical pharmacist, and nurse is required to prevent and manage post-operative bleeding.